Assessing mental health literacy and its association with help-seeking behavior among youth participants - Kartikananda, Prischa; Saniatuzzulfa, Rahmah (Universitas Ahmad Dahlan, 2025)
Approximately 15.5 million adolescents experience mental health problems, yet only 2.6% seek professional help. Without appropriate intervention, these difficulties may progress into more severe disorders, making help-seeking behavior critical for ensuring timely support. Youth Integrated Health Posts (Posyandu Remaja) serve as community-based platforms that promote adolescent health, including programs aimed at improving mental health literacy. However, low help-seeking behavior among youth attending these centers remains a persistent concern. This study aimed to examine the association between mental health literacy and help-seeking behavior among adolescents enrolled in Posyandu Remaja in Surakarta. Using purposive sampling, 114 adolescents participated in the study. Data were collected using adapted questionnaire-based scales assessing help-seeking behavior (α = 0.801) and mental health literacy (α = 0.528). Analysis was conducted using chi-square correlation tests in SPSS 25. The results indicated no statistically significant association between mental health literacy and help-seeking behavior among the participants, χ² = 0.631 (N = 114, p = 0.427). These findings suggest that improving mental health literacy alone may be insufficient to increase help-seeking tendencies among adolescents. Health service providers are encouraged to develop more comprehensive strategies beyond literacy-enhancing interventions. Future research may consider larger sample sizes, refined measurement tools, and the exploration of additional factors that may influence help-seeking behavior among youth in similar community settings.